Ensuring sustainable development for the German water sector: setting the stage for the risk-based sustainability management system (RSS). Issue 6 (3rd July 2018) - Geyler, Stefan; Kerber, Heide; Lux, Alexandra; Hedrich, Malte; Beck, Jessica; Möller, Kay; Selvakumar, Gevitha; Eller, Michael; Tocha, Christina; Sonnenburg, Alexander
Abstract: The service provision of drinking water and the disposal of waste water are severely challenged by changing framework conditions. Although service providers necessitate systematic information regarding sustainability risks, no available management tool accounts for them comprehensively. In the context of the project NaCoSi 'Ensuring Sustainability for Urban Water Systems', a risk-based sustainability management system (RSS) was developed. This paper aims to introduce RSS and to discuss its contribution towards companies' viability and transformation in the water sector. The paper describes the comprehensive self-screening approach of RSS, which is based on a causal-chain concept and comprises steps of risk analysis, monitoring and mitigation. Results of the testing phase suggest the validity of risk analysis and its effectiveness in deriving measures. Thus, RSS can help to improve the ability of service providers by analysing challenges and communicating them.